Phenolic compounds from Arthrospira platensis and Chlorella vulgaris enhance growth, digestive function, antioxidant capacity, and immune-related gene expression in Nile Tilapia - Eman Y. Mohammady; Mohamed R. Soaudy; Mohamed A. Elashry; Abeer M. A. Mahmoud; Soaad A. Sabae; Anisa Mitra; Ehab R. El-Haroun; Mohamed S. Hassaan (PLoS ONE, 2026)
Microalgae have many bioactive compounds as well as nutritional properties and have been used as a functional feed supplement to improve the health status of fish and their performance. Thus, the current trial was conducted to test the impacts of dietary supplement of phenolic compounds extracted from either Arthrospira platensis (PCA) or Chlorella vulgaris (PCC) on Nile tilapia (initial body weight: 1.52 ± 0.10 g) growth performance, digestive and hepatic antioxidant enzymes activity and immune related gene expression over a period of 70 days. Therefore, three isoproteic and isolipidic diets were formulated, and the experimental fish were fed these diets to satiation. The basal diet did not contain any supplements (control diet), whereas the other two diets were supplemented with 50 mg/kg of PCA and PCC, respectively. Compared with the control diet, growth parameters and survival rates were significantly enhanced (P < 0.05) by dietary supplementation of phenolic compounds of PCA and PCC. Most digestive enzymes were recorded in fish fed with phenolic extract of A. platensis . The ALT and AST values of fish fed diet supplemented with phenolic compounds extract from either PCA or PCC improved significantly compared with the basal diet. In addition, blood profile including serum total protein, albumin and globulin amounts augmented significantly in fish fed a diet enriched with phenolic compounds extracted of PCA and PCC ( P < 0.05). The maximum immune response parameters such as phagocytic activity, lysozyme and IgM activities were recorded for fish fed diets enriched with phenolic extract of PCA ( P < 0.05). The activities of antioxidant enzymes were significantly higher ( P < 0.05) in fish fed diets enriched with phenolic extract of A. platensis and C. vulgaris compared with the basal diet (control). Diet containing phenolic extract of PCA and PCC showed ( P < 0.05 ) up-regulated transcripts of interferon gamma ( IFN-γ ) and interleukin 1β ( IL-1 β ), but heat shock protein 70 ( HSP-70 ) genes were down-regulated. Fish fed phenolic extract of PCA showed the highest levels of IFN-γ and IL-1 β gene expression. Based on the findings achieved, the supplemental diets containing either PCA or PCC modulated growth performance, blood profile, enzymes activities, immune responses and related immune genes, with PCA providing the most effective response.